Early prosthetic valve endocarditis caused by Corynebacterium amycolatum: the first case reported in Brazil - Jaqueline Abel da Rocha; Natalia Chilinque Zambão da Silva; Ana SDN Silva; Rafael Guaresma Garrido; Beatriz Meurer Moreira; Ianick Souto Martins (Journal of Infection in Developing Countries)
Non-diphtheriae Corynebacterium species are usually considered as contaminants of clinical specimens due to their widely environmental distribution and colonization of the human skin and mucous membranes. However, these bacteria have been increasingly recognized as agents of life-threatening infections mainly in individuals in immunosuppressive conditions. These organisms have vast variation in morphology and biochemical reaction, characteristics that make the correct identification of Corynebacterium at the species level extremely difficult using conventional phenotypic methods. The precise identification of C. amycolatum requires approaches rarely available in conventional clinical microbiology laboratories, such as API Coryne system, 16s rRNA and rpoB gene sequencing. In this setting, MALDI-TOF, a quick, accurate, and relatively unexpansive molecular technique, arises as a cost-effective alternative for characterizing these agents. Here, a rare and lethal case of endocarditis caused by C. amycolatum is presented. This is the first case of infective endocarditis due to C. amycolatum reported in Brazil.